PEMANFAATAN MARKA JALAN UNTUK MENGATUR BATAS TERITORIAL PERILAKU PADA PASAR MINGGU PAGI (SUNDAY MORNING MARKET) UNIVERSITAS GADJAH MADA YOGYAKARTA (Studi Kasus : Jalan Olahraga Universitas Gadjah Mada Yogyakarta) - Ricardo, David (Universitas Atma Jaya Yogyakarta, 2014)
Abstract: This Research is one of methods to figure out the benefits from the use of marking road. A special handling is needed to the violations of Marking Road especially for populated area that located on lack of attention area. Sunday morning market of University of Gadjah Mada has tight activities every Sunday morning and Olahraga street is the study sample that represent other streets. This research using qualitative methods by gathering data field and interview to obtain results such as site size, history, behavior setting, behavior mapping, and personal space. The use of marking road must be related to territorial division of activities such as function and activity that is happening. Territory happened through a different process every its object. There are two divisions of territory for Sunday Market Morning that are Primary Territory and Secondary Territory. Primary Territory includes kiosk traders, parking attendants, and visitors. On the other hand, Secondary territory is a space that is used together such as secondary road or the divisor road. After the division of territories is obtained then the data is analyzed to get some alternatives. The alternatives are compared to get the pattern of territories that can be arranged through the use of Marking Road.Keywords: Marking Road, Territorial, Sunday Morning Market of Gadjah Mada University Abstrak: Penelitian ini merupakan salah satu cara untuk mengetahui manfaat dari penggunaan marka jalan. Pelanggaran terhadap marka jalan perlu penanganan khusus terutama daerah-daerah padat yang terdapat pada jalur jalan lingkungan yang kurang menjadi perhatian. Pasar Minggu Pagi (Sunday Morning Market) Universitas Gadjah Mada Yogyakarta termasuk memiliki kegiatan padat setiap minggu pagi dan jalan olahraga sebagai sampel penelitian mewakili jalan yang lain. Penelitian ini menggunakan metode kualitatif dengan mengumpulkan data lapangan dan wawancara sehingga mendapatkan data seperti ukuran site, sejarah, behavior setting, behavior mapping, dan personal space. Penggunaan marka jalan pasti berhubungan dengan pembagian batas teritori kegiatan seperti fungsi dan aktivitas yang terjadi. Teritori terjadi melalui proses yang berbeda-beda tiap objeknya. Pada Sunday Morning Market terdapat pembagian dua teritori yaitu primary territory dan secondary territory. Primary territory meliputi pedagang kios, pelaku parkir, dan pengunjung. Sedangkan secondary territory merupakan ruang yang dipakai bersama seperti jalan sekunder ataupun jalan pembagi. Setelah didapatkan pembagian teritorinya maka dianalisis dan mendapatkan beberapa alternatif. Alternatif tersebut dibandingkan sehingga mendapatkan pola teritori yang dapat diatur melalui penggunaan marka jalan.Kata kunci: Marka Jalan, Teritorial, Pasar Minggu Pagi Universitas Gadjah Mada